Geothermal heating : a handbook of engineering economics - Harrison, R.; Mortimer, N. D.; Smarason, O. B. (Pergamon Press, 1990)
To date all books on geothermics have emphasized its use for generating electricity, with applications of lower grade resources for direct heating meriting only a brief chapter. This book brings together research from a range of scientific journals and 'grey' literature to produce the first comprehensive text on geothermal heating. Economics form an important part of the book. It provides a step by step analysis of the various ways in which thermal waters can be used to provide space heating and of the advantages and disadvantages of different approaches. The final section of the book provides case studies of 31 geothermal heating schemes in France, USA and Iceland.